ChemInform Abstract: Aerobic Oxysulfonylation of Alkenes Leading to Secondary and Tertiary β‐Hydroxysulfones. Issue 48 (26th November 2013) - Lu, Qingquan; Zhang, Jian; Wei, Fuliang; Qi, Yue; Wang, Huamin; Liu, Zhiliang; Lei, Aiwen
Abstract The novel title reaction tolerates a wide range of functional groups and proceeds without any additional initiators.